Combination of different epistemic markers in Conan Doyle’s detective stories and in Vietnamese translational equivalents - Nguyễn Thị Thu Hạnh (My University, 2024)
Combination of different epistemic markers in Conan Doyle’s detective stories and in Vietnamese translational equivalents
Keywords: Epistemic markers